2019
DOI: 10.3390/socsci8080223
|View full text |Cite
|
Sign up to set email alerts
|

Big Data in Education. A Bibliometric Review

Abstract: The handling of a large amount of data to analyze certain behaviors is reaching a great popularity in the decade 2010–2020. This phenomenon has been called Big Data. In the field of education, the analysis of this large amount of data, generated to a greater extent by students, has begun to be introduced in order to improve the teaching–learning process. In this paper, it was proposed as an objective to analyze the scientific production on Big Data in education in the databases Web of Science (WOS), Scopus, ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 44 publications
2
17
0
2
Order By: Relevance
“…For instance, in a very recent bibliometric study [31], the authors mapped the research on IE over the past 25 years, and identified the topic of interest to us, the pre-service teacher education and their attitude toward IE, as one of the general themes addressed in IE literature, alongside others such as: IE in higher education settings, teaching for inclusion and in-service professional development on IE, and practices and principles of IE. All these bibliometric studies are published in recent years, more precisely between 2015 and 2020, which confirms the idea that the analysis of a large amount of data (what is called Big Data) has acquired great popularity in the last decade [36].…”
Section: Literature Analysissupporting
confidence: 57%
“…For instance, in a very recent bibliometric study [31], the authors mapped the research on IE over the past 25 years, and identified the topic of interest to us, the pre-service teacher education and their attitude toward IE, as one of the general themes addressed in IE literature, alongside others such as: IE in higher education settings, teaching for inclusion and in-service professional development on IE, and practices and principles of IE. All these bibliometric studies are published in recent years, more precisely between 2015 and 2020, which confirms the idea that the analysis of a large amount of data (what is called Big Data) has acquired great popularity in the last decade [36].…”
Section: Literature Analysissupporting
confidence: 57%
“…The final sample of publications was 240 (n = 240), 98 belonging to the Web of Science database and 142 to the Scopus database. This is a descriptive study based on the observation, systematization, and analysis of ten variables, taking into account other bibliometric studies in the field of education [44][45][46][47][48][49][50][51]. The time period considered for the bibliometric approach is linked to the date of enactment of the Sustainable Development Goals in 2015.…”
Section: Curating Phasementioning
confidence: 99%
“…El presente trabajo se ha centrado en el fomento de la lectura a través de las TIC, específicamente, siguiendo la línea de otros estudios de revisión que han analizado las TIC en educación de forma general (ALONSO-GARCÍA et al, 2019;MARÍN, 2020;MARÍN-MARÍN et al, 2019).…”
Section: Discusión Y Conclusionesunclassified